2021
DOI: 10.1111/cen.14613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of persistent subclinical hypothyroidism on clinical outcomes in non‐ST‐segment elevation acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Background: Data on the association of subclinical hypothyroidism (SCH) with the severity of coronary artery disease and major adverse cardiovascular and cerebral events (MACCE) in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) after percutaneous coronary intervention (PCI) are limited and conflicting. Objective: We established the baseline rate of SCH and followed the trajectory of thyroid-stimulating hormone (TSH) values during and after hospitalisation for PCI for up to six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Also proven from previous study showing that STEMI is associated with HTN, Family history and obesity in young adults specially in males it is found to be prevalent. 11,12,13 American heart association also showed that young adults having Higher blood pressure were more prone to develop Myocardial infarction with higher ST segment elevation. STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Also proven from previous study showing that STEMI is associated with HTN, Family history and obesity in young adults specially in males it is found to be prevalent. 11,12,13 American heart association also showed that young adults having Higher blood pressure were more prone to develop Myocardial infarction with higher ST segment elevation. STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Hyperthyroidism affects the rate and prognosis of ACS primarily by worsening ventricular function, inducing tachyarrhythmias and provoking vasospasm [ 20 ]. Hypothyroidism is associated with hypercholesterolemia, thereby increasing the likelihood of coronary heart disease and ACS [ 21 , 22 ]. Moreover, subclinical hypothyroidism is linked to abnormal global longitudinal strain in patients with heart failure, which is a common consequence of ACS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies compared the thrombolytic therapy with coronary intervention and found that the later one is more effective in terms of reduced mortality rate, stroke, and reinfarction [19,20]. In a study conducted by Han et al [21], increasing rate of mortality were observed in AMI patients with RBBB treated with angioplasty.…”
Section: Discussionmentioning
confidence: 99%